“Disabled People Are Sexual Citizens Too”: Supporting Sexual Identity, Well-being, and Safety for Disabled Young People - Sonali Shah (Frontiers in Education, 2017)
Disabled young people are sexual beings, and deserve equal rights and opportunities to have control over, choices about, and access to their sexuality, sexual expression, and fulfilling relationships throughout their lives. This is critical to their overall physical, emotional, and social health and well-being. However, societal misconceptions of disabled bodies being non-normative, other, or deviant has somewhat shaped how the sexuality of disabled people has been constructed as problematic under the public gaze. The pervasive belief that disabled people are asexual creates barriers to sexual citizenship for disabled young people, thereby causing them to have lower levels of sexual knowledge and inadequate sex education compared to their non-disabled peers. As a consequence, they are more vulnerable to “bad sex”—relationships, which are considered to be exploitative and disempowering in different ways. Access to good sex and relationships education for disabled young people is, therefore, not only important for them to learn about sexual rights, sexual identity, and sexual expression but also about how to ensure their sexual safety. In so doing, it will contribute to the empowerment and societal recognition of disabled people as sexual beings, and also help them resist and report sexual violence. Therefore, it is critical that parents, educationalists, and health and social care professionals are aware and appropriately equipped with knowledge and resources to formally educate disabled young people about sexuality and well-being on par to their non-disabled peers.